The impact of thiopurine S-methyltransferase polymorphisms on azathioprine dose 1 year after renal transplantation. - Fabre, M; Jones, D; Bunce, M; Morris, P; Friend, P; Welsh, K; Marshall, SE (2004)
Azathioprine metabolism is influenced by activity of the enzyme thiopurine S-methyltransferase (TPMT), which varies markedly between individuals. In this study we examined the influence of TPMT gene polymorphisms on azathioprine dose 1 year after renal transplantation. TPMT coding and promoter genotypes were determined using PCR-based assays. Azathioprine dose, white cell count, and intercurrent events throughout the first year after renal transplantation were ascertained from contemporaneous clinical notes. All patients analysed ( n=172) received an initial azathioprine dose of 1.5 mg/kg per day. Twelve individuals with one variant TPMT coding allele were detected (*3A n=11, *3C n=1). Of these, 58% required azathioprine dose reduction because of leucopenia, compared to only 30% of homozygous wild-type patients ( P=0.04). A significant correlation between the presence of >/=11 variable number tandem repeats (VNTRs) in the TPMT promoter and reduction in azathioprine dose was also identified ( P=0.001). We concluded that when azathioprine is administered at an initial dose of 1.5 mg/kg per day, both coding and promoter TPMT polymorphisms influence the dose tolerated.